COMMUNITY EMPOWERMENT THROUGH MAKING SHREDDED CATFISH AS A SOLUTION TO INCREASE THE ADDED VALUE OF FISHERY PRODUCTS IN CIBADUNG, GUNUNG SINDUR, BOGOR - M. Averros Azzam Al Islami; Alviana Jami’atus Syifah; Arni Andriani; Duta Arindya Naresti; Lusiana Febriati Nggepe; M. Uwais Hidayatullah; Neni Nuraeni; Sastri Lisma Dewi; Yunita Sanci Taniu (LPPM STAI Muhammadiyah Probolinggo, 2025)
This activity aims to increase the added value of fishery products through training in making shredded catfish for the people of Cibadung Village, Gunung Sindur District, Bogor Regency. The problems identified are the lack of optimal utilization of catfish cultivation products and the lack of innovation in processed products with high economic value. The method of activity includes observation of local potential, socialization, the practice of making shredded catfish, to community work titles. The production process is carried out through the stages of boiling, refining, mixing spices, and frying to produce dry, savory, and long-lasting shredded meat. The results of the activity showed that the